Assessment of microalga biofilms for simultaneous remediation and biofuel generation in mine tailings water. (June 2017) - Palma, H.; Killoran, E.; Sheehan, M.; Berner, F.; Heimann, K.
Graphical abstract: Highlights: Endemic microalgae biofilms grown in tailings water: fuel and metal remediation. High carbohydrate yield (40.0%), potential for increased lipid yield (6.7–19.5%). Up to 24.8%, 10.5%, 24.8% and 26.4% reduction in Ni, Co, Mn, and Sr. Productivity (0.77 ± 0.07 g AFDW/(m 2 .day)) shows promising potential. Abstract: Microalgae crops can generate a biochemical profile of high energy density and may be used for remediation of contaminated waste waters. This manuscript presents a laboratory-scale investigation into the potential for growing endemic microalgae biofilms in phosphorus-enriched nickel refinery tailings water, with an emphasis on product potential and the remediation of heavy metals. The dominant species of the consortia was a Chlorella -like microalga. The growth was monitored over time, with a productivity (0.77 ± 0.07 g AFDW.m −2 .day −1 ) showing promising potential. The biochemical profile of biomass had a high total carbohydrate yield (40.0%), and a potential for increased lipid yields (6.7–19.5%). Biofilms showed a significant potential for the removal of heavy metals (Ni, Co, Mn, Sr) from the waste water with 24.8%, 10.5%, 24.8% and 26.4% reduction in Ni, Co, Mn and Sr, respectively. Results highlight significant potential for large-scale biofilm biomass production using metal-laden nickel refinery waste waters.